Development and Evaluation of the Game LEAGUE OF QUALITY: ISO/IEC 25000 in an Educational Context - Masson, Eloisa Toffano Seidel; Haddad, Antonio; Calazans, Angelica Toffano S.; Paldes, Roberto Avila; Canedo, Edna Dias (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
Context: Teaching software quality concepts can be challenging due to their abstract nature and limited engagement with traditional instructional methods. To address this, educational games have emerged as an effective strategy for improving motivation and learning outcomes, particularly in Information Technology programs. Aims: This paper reports on the development and evaluation of the educational game LEAGUE OF QUALITY: ISO/IEC 25000, which aims to teach software product quality concepts based on ISO/IEC 25000. The goal is to introduce diversity into the course and enhance students’ skills, engagement, and knowledge. Method: The development of the game followed four phases: pre-production, pilot testing, production, and finalization. The game was applied in classroom settings with IT students at a Brazilian university. Data was collected from both students and professors regarding their perceptions of the game’s effectiveness and usability. Results: Most students reported that the concepts presented in the game were applicable to real-world professional scenarios. They found the dynamics of the game clear, accessible, and engaging, contributing positively to their understanding. The game provided a better learning experience, especially for students with little prior knowledge. Professors also observed increased motivation, participation, and improved learning outcomes. Conclusions: LEAGUE OF QUALITY proved to be an effective and engaging educational tool for teaching software product quality. It enhanced student motivation, especially among those with limited prior knowledge, and promoted better understanding and retention of key concepts. Both students and professors reported increased engagement, with students highlighting the game’s relevance to real-world practice and its positive impact on the learning experience.